The effect of shielding material density in muon tomography - Sitti Yani; Dadan Hidayatuloh; Tony Sumaryada (Lambung Mangkurat University Press, 2023)
In recent years, the use of high-penetrate cosmic-ray muons has been used in many applications to investigate the internal structure and composition of large material. The muon attenuation is based on multiple Coulomb scattering. This study was aimed to investigate the effect of massive shielding material composition in muon tomography. Muon with various energies between 1 MeV to 100 MeV was used as a source located directly above the shielding material with different density and composition. The output of scattered muon was scored in 2 and 5 km after the material. The simulation was performed using particle and heavy ion transport system (PHITS) software developed by Japan Atomic Energy Agency. The attenuation and scattering of the muon depends predominantly on the shielding material density. The muon energy and flux was decreased with increasing depth of the muon detector. This muon tomography can be applied in investigating the structure and internal composition of unknown materials such as volcanic structures in Indonesia.